The use of museum skins for genomic analyses of temporal genetic diversity in wild species - Stronen A. V.; Iacolina L.; Pertoldi C.; Kusza S.; Hulva P.; Dykyy I.; Kojola I.; Faurby S. (Conservation Genetics Resources, 2019)
Analyses of museum specimens can help illuminate temporal changes in wildlife genetics and distributions, and the objective of our study was to evaluate the suitability of skin samples from the past century for genomic analyses. We examined two European species with extensive genomic resources and existing data: the wild boar (Sus scrofa) and the wolf (Canis lupus). Populations of both species declined during the twentieth century, followed by a strong recovery. Moreover, Carpathian Mountain wolves are genetically divergent from Northern European lowland wolves, and their evolutionary history is incompletely understood. We analysed genetic variation from skins of 14 European and Near Eastern wild boars (1903–1948) and 18 Carpathian and Northern wolves (1938–1998). Samples were genotyped in duplicates with standard Illumina single nucleotide polymorphism (SNP) arrays (wild boar 60 K and wolves 170 K), and we retained SNPs with a genotyping rate of > 90%. We obtained a final set of 1595 SNPs for six wild boars (genotyping rate 0.99) and 1806 SNPs for 18 wolves (genotyping rate 0.96). We merged the best performing duplicate with modern data and calculated polymorphism (P), observed (HO) and expected (HE) heterozygosity per population. Our findings underline the difficulties in obtaining quality genomic profiles from museum skins, though a limited number of SNPs provided insights for future research. Wild boars exhibited lower polymorphism in historical than modern samples. In contrast, patterns in wolves appeared spatial rather than temporal, with higher P, HO and HE observed in Carpathian than Northern wolves across historical and modern samples.